Practical research 2 - Solano, Irene P.; David, Oliver M. (Makati City : Diwa Learning Systems, Inc., 2019)
"This textbook is a continuation of the topics covered in Practical Research 1. While PR 1 discusses qualitative research, PR 2 focuses on quantitative research. This is divided into two units: Unit 1: Writing the Research Proposal, Unit 2: Writing the final Research Report."
Includes bibliography.
Keywords: Research -- methodology